Effect of producer's innovation and vendor's sales promotion activities for perishable items under quadratic demand: a centralised vs. decentralised approach. (30th September 2022) - Jani, Mrudul Y.; Patel, Heta A.; Betheja, Manish R.; Chaudhari, Urmila; Pandya, Bhargav
This research focuses on a single producer-vendor supply chain. To increase the revenue and demand of the product, the producer employs innovation and the vendor employs sales promotion. In this article, demand for the product is predetermined to be quadratic. This paper examines a supply chain for innovation activity, sales promotion activity, and replenishment time, using both centralised and decentralised approaches, with products deteriorating at a constant rate. As the centralised approach reduces the vendor's total profit, the producer tries to convince the vendor by offering a credit facility, discount and profit sharing. The key ambition is to calculate the optimum replenishment time, producer's innovation activity, and vendor's sales promotion activity by using the classical optimisation algorithm that helps to maximise the total profit of a supply chain. The numerical example is solved for both centralised and decentralised approach, and the sensitivity analysis of major parameters are eventually analysed.